Teacher’s Roles Implemented in Teaching Children and Teenager Classes in Petra Language Center (PLC) - Evelyn Listiyani; Julia Eka Rini (Kata Kita: Journal of Language, Literature, and Teaching, 2020)
This study analyzed the implementation of teacher’s roles at Petra Language Center (PLC). There were two classes with five to six students in each class taking part in this study. The main theories for this study are from Harmer’s (2001 & 2007) on teacher’s roles. The method used was qualitative approach. The researcher investigated the teacher’s roles implemented in children and teenager classes and analyzed the similarities and differences. The findings revealed that there are several similarities and differences. The main similarity is that the teacher implemented the same number of teacher’s roles types for both classes. The second one is that the teacher’s role as an organizer was more or less equally the same. The differences are in the number of occurrence of each type, the context and the way the teacher implemented those roles in both classes. Additionally, the findings also showed that the most important thing is that the teacher should be able to adjust the roles according to the classroom situation and activities. Keywords: Teacher’s roles, children class, teenager class, similarities and differences of teacher’s roles